Variabilité spatio-temporelle de la qualité de l’eau potable des petits réseaux : facteurs explicatifs et développement d'outils de gestion - Scheili, Anna (Université Laval, 2015)
This thesis focuses on the determination of factors that impact the spatio-temporal variability of drinking water quality in small systems and on the development of management tools intended to operators. Data was provided by sampling campaigns conducted in 25 small systems in two Canadian provinces (Quebec and Newfoundland and Labrador). The first chapter draws a spatio-temporal portrait of raw and drinking water quality in the systems under study. Some factors affecting the quality of drinking water are identified. In the second chapter, a drinking water quality index is developed. Four customized monitoring scenarios are proposed according to the specific needs of small systems, which allow the appropriate representation of global drinking water quality. The third chapter identifies raw water quality parameters and climate factors that have an important impact on the temporal variability of drinking water quality. Based on these factors, a logistic regression model allows the development of a tool that estimates the probability of the deterioration of drinking water quality. The last chapter considers human operational factors as impact factors in drinking water quality management. A categorization leads to the determination of the most important human operational factors contributing to drinking water quality. A multi-level model is applied to evaluate the relative contribution of human operational factors in comparison to the impact of raw water quality and treatment. Finally, the impact of the temporal variability of human operational factors on drinking water quality is investigated. Keywords: Water quality, drinking water, small systems, spatio-temporal variability, water quality index, climate factors, human operational factors, management tools. Cette thèse est consacrée à la détermination des facteurs responsables de la variabilité spatio-temporelle de la qualité de l’eau potable dans les petits réseaux de distribution et au développement d’outils de gestion destinés aux opérateurs. Afin de réaliser ...